RISK MANAGEMENT ON COCOA SUPPLY CHAIN IN MSME KAMPUNG COKLAT SENARA, LOMBOK, INDONESIA - Fatimah, Anisah Nur; Aditiawati, Pingkan; Simatupang, Togar Mangihut (Universitas Nusa Cendana, 2025)
Kampung Cokelat Senara (KCS) is a Micro Small and Medium Enterprise (MSME) that processes cocoa beans to produce chocolate products. The imbalance of supply and demand increases risks in the primary actors of the supply chain. This study aims to identify, assess, and determine risk factors through FMEA, and determine risk mitigation strategies for the cocoa supply chain in KCS through an Analytical Hierarchy Process (AHP) analysis. Ten risk factors were identified for cocoa farmers, nine risk factors for cocoa product manufacturers, and seven risk factors for distributors/retailers. The priority risk factor at the cocoa farmer level is pests and disease damage. The priority risk factor at the producer level is the uncertain supply of raw materials. The priority risk factor at the distributor/retailer level is fluctuating buying interest. Cocoa farmers are prioritized actors in the supply chain. The priority strategy for supply chain risk management at the farm level is the crop intensification program. The priority strategy for supply chain risk management at the producer level is an expanded partnership with farmers. The priority strategy for supply chain risk management at the distributor/retailer level is product specialization. Keywords : Analytical Hierachy Process; Cocoa; Risk; MSME; Supply Chain